Scaling ALF-LB with Model Size and Expert Count in Code Generation Benchmarks - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 12 peer-reviewed papers addressing the following research question: How does the ALF-LB method scale with increasing model size and number of experts in terms of training stability and final accuracy on the MBPP code generation benchmark compared to traditional MoE. 15 claims were extracted from source literature; 1 was independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 4.4/10. This report i
Machine-generated literature synthesis.